2018
DOI: 10.1080/14737140.2018.1524297
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib as a therapy for unresectable hepatocellular carcinoma

Abstract: Since 2007 Sorafenib has represented the only approved drug for first-line treatment of advanced hepatocellular carcinoma (HCC). Lenvatinib, an orally active inhibitor of multiple receptor tyrosine kinases (VEGFR 1-3, FGFR 1-4, PDGFRa, RET and KIT), showed preclinical and clinical activity in the treatment of solid tumors, including HCC. Areas covered: In this review, we summarize the current therapeutic paradigm for the systemic treatment of advanced HCC, focusing on Lenvatinib pre-clinical and clinical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…This implied that patients with CK19-positive HCC could benefit from sorafenib administration after surgery. As Govaere et al 55 demonstrated that CK19 could be progressed through PDGFRα-LAMB1-CK19 axis, inhibitors of PDGFRα such as imatinib 76 , regorafenib 77 and lenvatinib 78 might exert specific effect on CK19-positive HCC. Therefore, the above-named first-line or second-line multi-targeted tyrosine kinase inhibitors (TKI) approved by FDA for HCC are supposed to have therapeutic priority to CK19-positive HCC.…”
Section: The Detective and Therapeutic Strategy For Ck19 Positive Hccmentioning
confidence: 99%
“…This implied that patients with CK19-positive HCC could benefit from sorafenib administration after surgery. As Govaere et al 55 demonstrated that CK19 could be progressed through PDGFRα-LAMB1-CK19 axis, inhibitors of PDGFRα such as imatinib 76 , regorafenib 77 and lenvatinib 78 might exert specific effect on CK19-positive HCC. Therefore, the above-named first-line or second-line multi-targeted tyrosine kinase inhibitors (TKI) approved by FDA for HCC are supposed to have therapeutic priority to CK19-positive HCC.…”
Section: The Detective and Therapeutic Strategy For Ck19 Positive Hccmentioning
confidence: 99%
“…At first, lenvatinib was approved for the treatment of radioiodine-refractory differentiated thyroid cancer, as a single agent, and for the treatment of advanced renal cell carcinoma in combination with everolimus[79,88-90]. On August 2018, based on positive results of the REFLECT trial (NCT01761266), the FDA approved lenvatinib as a first-line treatment in patients with advanced and unresectable HCC[91,92].…”
Section: Pharmacogenetics Of Approved Drugsmentioning
confidence: 99%
“…Additional multi-kinase inhibitors recently approved for HCC treatment include regorafenib (for secondary treatment after sorafenib), as well as levatinib (another first-line drug to treat HCC besides sorafenib). However, neither provide much more additional benefit than sorafenib treatment[13,14]. As such, better treatment options are still needed.…”
Section: Introductionmentioning
confidence: 99%